Worldwide pesticide usage and its impacts on ecosystem - Sharma, Anket; Kumar, Vinod; Shahzad, Babar; Tanveer, Mohsin; Sidhu, Gagan Preet Singh; Handa, Neha; Kohli, Sukhmeen Kaur; Yadav, Poonam; Bali, Aditi Shreeya; Parihar, Ripu Daman; Dar, Owias Iqbal; Singh, Kirpal; et al. (SN applied sciences, 2019)
Pesticides are extensively used in modern agriculture and are an effective and economical way to enhance the yield quality and quantity, thus ensuring food security for the ever-growing population around the globe. Approximately, 2 million tonnes of pesticides are utilized annually worldwide, where China is the major contributing country, followed by the USA and Argentina, which is increasing rapidly. However, by the year 2020, the global pesticide usage has been estimated to increase up to 3.5 million tonnes. Although pesticides are beneficial for crop production point of view, extensive use of pesticides can possess serious consequences because of their bio-magnification and persistent nature. Diverse pesticides directly or indirectly polluted air, water, soil and overall ecosystem which cause serious health hazard for living being. In the present manuscript, an attempt has been made to critically review the global usage of different pesticides and their major adverse impacts on ecosystem, which will provide guidance for a wide range of researchers in this area.